Signature sequence for DS-CDMA cellular system - Chen, Jie. (2008)
The major technology behind code-division multiple access (CDMA) is the spread-spectrum multiple access method, which allows signals occupying the same frequency bandwidth to be transmitted simultaneously without interfering with each other. The direct-sequence CDMA (DS-CDMA) scheme is the method currently being used by commercial cellular mobile phone systems. Every user in each user group is assigned its own code, that user codes are approximately orthogonal so that the cross-correlation of any two different codes tends to be zeros. Hence, all subscribers can share the full spectrum of the resource asynchronously.